Estética y política en Jacques Rancière - Lévêque, JEAN-CLAUDE (Escritura e Imagen, 2005)
The french philosopher Jacques Rancière has developed an interesting thesis about the nature of images. In Rancière’s thought, the sense of images are the effect of a dialectical mouvement, an immanent process that has no reference to a metaphysical ground (Grund). Rancière’s critique of the concept of sublime, applied by Lyotard to some issues of contemporary art, denonces the ambiguity of the concept of «irrepresentability»; the thesis of Lyotard remains in fact an hegelian one and finally submits the aesthetics to ethics.